CCAFS support APEC economies to develop and adopt a multi-year plan on climate change and food security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
CCAFS (FP2, RPL SEA, CIAT) provided strategic support to APEC throughout 2017 in the establishment of a Multi Year Action Plan for Climate Change and Food Security for 2018-2021, which was endorsed in the November APEC Summit. CCAFS experts helped organise 3 stakeholder consultations, facilitated the dialogue and agreement on joint areas of priority, inputted on the final MYAP document, and presented it in Food Security Week in Vietnam in August.